糖尿病における創傷治癒遅延に対するプロスタグランジンD2合成酵素の関与について - 鎌内, 朋子; 松本, 晴樹; 裏出, 良博; 有竹, 浩介 (日本薬理学会年会要旨集, 2022)
Delayed wound healing is a major problem in patients with diabetes melitus, which significantly impairs their quality of life. Prostaglandin (PG) D2 is a major inflammatory lipid mediator synthesized by hematopoietic PGD2 synthase (HPGDS) from PGH2, a common precursor of all of PGs. In the present study, we investigated the role of PGD2 in cutaneous wound healing in streptozotocin (STZ)-induced diabetic mice. C57BL/6 mice were injected with 50 mg/kg of STZ intraperitoneally daily for 5 days. Four weeks after the injection of STZ, a full thickness wound was created with an 8-mm diameter biopsy punch on the dorsal of mice showing the hyperglycemia (>300 mg/dL). Wound healing was significantly decelerated in diabetic mice compared with non-diabetic mice. The mRNAs of HPGDS, Cyclooxygenase (COX) 1, COX2, DP1 and DP2 receptors in mouse skin were measured by quantitative PCR. The skin of diabetic mice had significantly increased mRNAs of HPGDS and DP2 receptors as compared with the skin of non-diabetic mice. In addition, there was no significant change in the amount of DP1 receptors mRNA and COX1 mRNA, but the amount of COX2 mRNA tended to increase. In addition, immunohistochemical analysis revealed that HPGDS was upregulated in epidermal Langerhans cells of diabetic mice. These results suggest  that in hyperglycemic skin, production of PGD2 is increased in Langerhans cell and may be involved in delayed inflammation via DP2 receptors.